Missing Queens: Gender, Dynasty and Power in Vandal Africa. (Gender & History, 2022)
This paper reconsiders a curious aspect of the Vandal kingdom of North Africa (439–533 ce): the total absence of women called Vandals in extant sources. It argues that these missing Vandal women are the women of the Hasding royal dynasty. The non‐application of the ethnic terminology to the consorts, sisters and daughters of kings and princes corresponds to a broader dearth of contemporary discussions of their political agency. This reduced visibility reflects particular structural features of Vandal kingship – and, in particular, its succession arrangements – which reduced the significance of queens and princesses in both the representation and practice of governance at the royal court in Carthage.